2005
DOI: 10.1007/s00417-005-0104-6
|View full text |Cite
|
Sign up to set email alerts
|

No changes in anatomical and functional glaucoma evaluation after trabeculectomy

Abstract: No significant change on any test variable was detected after glaucoma filtration surgery. Trabeculectomy does not appear to influence standard automated perimetry, frequency doubling technology perimetry, scanning laser polarimetry and confocal scanning laser ophthalmoscopy (HRT II) results after a 4.5-month period of surgery in early to moderate glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2005
2005
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
1
12
0
2
Order By: Relevance
“…The exception was some patients undergoing glaucoma surgery and experiencing a marked drop in intraocular pressure (Pederson & Herschler 1982;Schwartz et al 1985;Katz et al 1989;Parrow et al 1992;Park et al 1997;Lesk et al 1999;Kotecha et al 2001Kotecha et al , 2009Wu et al 2002;Tavares et al 2006;Harju et al 2008;Yuen & Buys 2010). These patients could also show an improvement in function (Jindal et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exception was some patients undergoing glaucoma surgery and experiencing a marked drop in intraocular pressure (Pederson & Herschler 1982;Schwartz et al 1985;Katz et al 1989;Parrow et al 1992;Park et al 1997;Lesk et al 1999;Kotecha et al 2001Kotecha et al , 2009Wu et al 2002;Tavares et al 2006;Harju et al 2008;Yuen & Buys 2010). These patients could also show an improvement in function (Jindal et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has been discussed that in these very young children, the optic nerve scleral canal was still elastic, so that a relatively short-term increase in intraocular pressure could lead to a reversible enlargement of the optic disc, and because of the correlation between disc size and cup size, secondarily to a reversible enlargement of the optic cup (Quigley 1977;Robin & Quigley 1979). Clinical studies on adult patients with glaucoma have described an increase in the neuroretinal rim and, complementarily, a decrease in the optic cup in adult patients after reduction in an highly elevated intraocular pressure (Pederson & Herschler 1982;Schwartz et al 1985;Katz et al 1989;Parrow et al 1992;Park et al 1997;Lesk et al 1999;Kotecha et al 2001Kotecha et al , 2009Wu et al 2002;Tavares et al 2006;Harju et al 2008;Yuen & Buys 2010). As a corollary, Azuara-Blanco found that a short-term increase in intraocular pressure from about 13 mmHg to about 35 mmHg resulted in a significant (p < 0.05) enlargement in the optic disc cupping (Azuara-Blanco et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…An improvement in the results of these tests following IOP reduction was observed in some studies [6,11,[14][15][16], but could not be confirmed in others [17,18].…”
Section: Introductionmentioning
confidence: 90%
“…Various diagnostic tests have been performed for further assessment of the functional and anatomical changes after IOP-lowering therapy, such as optical coherence tomography (OCT), standard automated perimetry (SAP) and measurements of the spatial contrast sensitivity threshold [6,11,[14][15][16][17][18]. An improvement in the results of these tests following IOP reduction was observed in some studies [6,11,[14][15][16], but could not be confirmed in others [17,18].…”
Section: Introductionmentioning
confidence: 98%
“…Para estudo da CFN, temos o polarímetro de varredura a laser com compensador variável de córnea (GDx VCC). Contudo, esses dois últimos aparelhos não possuem programas específicos para avaliação de progressão (121)(122)(123) .…”
Section: Seguimentounclassified